Ameliorative Effect of Parabacteroides distaxsonis on Cognitive Impairment Caused by Type 2 Diabetes Mellitus - DU Yue, ZHAO Zhongna, LIU Xuebo (Shipin Kexue, 2025)
Objective: To investigate the ameliorative effect and mechanism of Parabacteroides distasonis on cognitive impairment caused by type 2 diabetes mellitus (T2DM). Methods: Ten-week-old db/db mice were administered with P. distasonis (1 × 109 CFU/mL) by gavage for 5 weeks. During this period, the body mass and insulin resistance of all mice were monitored. Behavioral tests were conducted to evaluate changes in spatial memory, recognition memory, and working memory capacity. Furthermore, serum levels of insulin, total cholesterol (TC), low-density lipoprotein cholesterol (LDL-C), and triglycerides (TG) were measured, along with morphological and inflammatory changes in liver, brain, and colon tissues. Additionally, changes in serum bile acids and the mRNA expression of genes associated with bile acid metabolism were examined. Results: Intervention with P. distasonis effectively regulated blood glucose homeostasis and insulin resistance in db/db mice. It reduced the mass of adipose tissue, decreased hepatic fat accumulation, and lowered serum concentrations of TC, LDL-C and TG. The intervention restored colonic morphology, protected intestinal barrier integrity, and reduced intestinal inflammation. It also promoted bile acid production and activated bile acid metabolism-related signaling pathways. Meanwhile, it suppressed cerebral neuroinflammation and oxidative stress, repaired neuronal damage, and significantly alleviated cognitive impairment. Conclusion: P. distasonis intervention can lower blood glucose, alleviate insulin resistance, and mitigate glucose and lipid metabolic disorders as well as cognitive dysfunction induced by T2DM, showing potential as a new generation of probiotics for diabetic management.